(untitled) (Journal of NELTA, 2022)
Since 2016, the development of artiﬁcial intelligence (AI) has been strong and pervasive, including its roles in business and education. In ELT, in particular, several machine learning models have been implemented such as speech recognition, grammar correction, chatbots, and translation. ELT is in the middle of a rapid and disruptive change and the magnitude of which is paramount that we have never witnessed before. Under this situation, ELT practitioners may have to acquire additional skills and competencies so as to be relevant and thrive in this rapid change and move the ﬁeld forward to the next level. In this paper, the researcher proposes ELT 3.0, a new vision where working with the machines needs to be incorporated into the existing roles of the ELT teachers.